Blockchain-based traffic surveillance footage authenticity detection system - Bin Moshiur, Tasnimul; Ullah, Mohammad Zafar; Nawar, Nahian; Tazwar, Tawsif Muhammed; Nanjiba, Rifah (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.